2014
DOI: 10.1289/ehp.1307009
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Frameworks for Monitoring Antibiotic Resistance in Aquatic Environments

Abstract: Background: High-throughput genomic technologies offer new approaches for environmental health monitoring, including metagenomic surveillance of antibiotic resistance determinants (ARDs). Although natural environments serve as reservoirs for antibiotic resistance genes that can be transferred to pathogenic and human commensal bacteria, monitoring of these determinants has been infrequent and incomplete. Furthermore, surveillance efforts have not been integrated into public health decision making.Objectives: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 40 publications
0
55
0
1
Order By: Relevance
“…Sediments provide natural areas of high microbial density, which is of particular concern considered the elevated persistence and accumulation of antimicrobial resistance (AMR). Port et al (2014) estimated the potential for gene transfer and pathogenicity potential from sediment fecal bacteria from pyrosequencing datasets of sediments. This is pertinent for developing suitable baseline AMR/pathogenicity levels used to inform policy makers on fecally derived hazardous microorganisms/pathogens in sediments.…”
Section: Discussionmentioning
confidence: 99%
“…Sediments provide natural areas of high microbial density, which is of particular concern considered the elevated persistence and accumulation of antimicrobial resistance (AMR). Port et al (2014) estimated the potential for gene transfer and pathogenicity potential from sediment fecal bacteria from pyrosequencing datasets of sediments. This is pertinent for developing suitable baseline AMR/pathogenicity levels used to inform policy makers on fecally derived hazardous microorganisms/pathogens in sediments.…”
Section: Discussionmentioning
confidence: 99%
“…The in-vestment on antibiotic resistance monitoring would not be a stray effort, since it could be framed in a broader context of ongoing problems associated with water quality, related not only with pollution but also with climate variability, among other, and that require the action of regulatory authorities at local, national, and global scales (GEMS-Water 2014). In re-search laboratories, high-throughput qPCR and metagenomics analyses of ARG are increasingly the state of the art (Nesme et al 2014;Port et al 2014;Li et al 2015). and these will be important contributions to understand antibiotic resistance evolution.…”
Section: Methods Harmonization and Data Sharingmentioning
confidence: 99%
“…In case of coastal sea, although the contaminated waters are significantly diluted, fecal-derived bacteria, such as E. coli , remain viable ARG reservoirs of concern (Alves et al; Kappell et al; Ghaderpour et al). ARB and ARGs are known to occur in aquatic environments without antibiotic contaminations (Port et al, 2014). ARBs and ARGs flow into rivers, groundwater and marine environments by influx of WWTP effluent as mentioned above.…”
mentioning
confidence: 99%
“…Suzuki et al (2013) and Suzuki et al found that the defining features of ARGs tend to be distinct between culturable and yet-to-be cultured bacteria. The recent advent of next-generation DNA sequencing and metagenomics poises the scientific community on the verge of a major advance in understanding the behavior of ARGs in the environment (D'Costa et al, 2006; Port et al, 2014). However, deep sequencing and the capacity to perform high-throughput bioinformatics analyses are required to match ARGs with their bacterial hosts.…”
mentioning
confidence: 99%